Correlation analysis of serum IgG4 expression level with renal function and micro inflammatory status in patients with IgG4-related nephropathy - Jiao Qi; Shan-shan Xu; Xiao-xing Duan; Hai-xin Wang; Yan Meng; Jian-rong Zhao (Linchuang shenzangbing zazhi, 2024)
Objective To explore the correlation between serum level of immunoglobulin G4 （IgG4）, renal function and micro inflammatory status in patients with IgG4-related nephropathy. Methods From January 2018 to August 2022, 60 patients hsopiatlized with IgG4-related nephropathy were selected as study group while another 60 healthy volunteers chosen as control group in 1∶1 ratio based upon propensity matching. Serum level of IgG4, renal function parameters of serum creatinine （Scr）, blood urea nitrogen （BUN）, estimated glomerular filtration rate （eGFR） and 24 h urinary total protein quantification （24 hUTP） and micro inflammatory status [including interleukin-6 （IL-6）, high-sensitivity C-reactive protein （hs-CRP） and tumor necrosis factor-α （TNF-α）] were detected in both groups. Serum level of IgG4, renal function and micro inflammatory status were compared between two groups. Pearson’s method was employed for examining the correlation between serum level of IgG4, renal function and micro inflammatory status in study group. Logistic regression analysis was performed for determining the risk factors for renal insufficiency. Results Serum level of IgG4 [（67.75 ± 18.63） mg/L vs （6.54 ± 1.19） mg/L], Scr [（182.75 ± 32.69） μmol/L vs （75.40 ± 15.61） μmol/L], BUN [（10.15 ± 2.90） mmol/L vs （5.28 ± 1.04） mmol/L], IL-6 [（5.18 ± 1.04） ng/L vs （0.40 ± 0.05） ng/L], hs-CRP [（24.69 ± 5.06） mg/L vs （4.58 ± 0.92） mg/L], TNF-α [（6.85 ± 1.79） μg/L vs （1.18 ± 0.21） μg/L] and 24 hUTP [（182.75 ± 32.69） mg vs （89.75 ± 12.36） mg] were higher in study group than those in control group （P＜0.05）; eGFR was lower than that in control group [（90.10 ± 9.87） mL·min−1·（1.73 m2）−1 vs （104.36 ± 20.15） mL·min−1·（1.73 m2）−1] （P＜0.05）. Serum level of IgG4 was correlated positively with Scr, BUN, 24 hUTP, IL-6, hs-CRP and TNF-α （r = 0.586, 0.543, 0.575, 0.602, 0.596, 0.574, P＜0.05） and negatively with eGFR in study group （r = −0.602, P＜0.05）. The incidence of renal insufficiency was 78.33% in study group. Course of disease, hypertension and serum level of IgG4 were the influencing factors of renal insufficiency （OR = 3.190, 2.401, 3.466, P＜0.05）. Conclusions An elevated serum level of IgG4 in patients with IgG4-related nephropathy is correlated with renal function and micro inflammatory status. And course of disease, concurrent hypertension and serum IgG4 level are the influencing factors for renal insufficiency.